Phenotypes of hypofrontality in older female fragile X premutation carriers. Issue 2 (24th September 2013) - Yang, Jin‐Chen; Simon, Christa; Niu, Yu‐Qiong; Bogost, Mark; Schneider, Andrea; Tassone, Flora; Seritan, Andreea; Grigsby, Jim; Hagerman, Paul J.; Hagerman, Randi J.; Olichney, John M.
<x xml:space="preserve">Abstract</x> Objective To investigate the nature of cognitive impairments and underlying brain mechanisms in older female fragile X premutation carriers with and without fragile X‐associated tremor/ataxia syndrome (FXTAS). Methods Extensive neuropsychological testing and cognitive event‐related brain potentials (ERPs; particularly, the auditory P300) were examined in 84 female participants: 33 fragile X premutation carriers with FXTAS (mean age = 62.8 years), 25 premutation carriers without FXTAS (mean age = 55.4 years), and 26 normal healthy controls (mean age = 59.3 years). Results Both premutation groups exhibited executive dysfunction on the Behavioral Dyscontrol Scale, with subtle impairments in inhibition and performance monitoring in female carriers without FXTAS, and more substantial deficits in FXTAS women. However, the female carrier group without FXTAS showed more pronounced deficiencies in working memory. Abnormal ERPs were recorded over the frontal lobes, where FXTAS patients showed both P300 amplitude reduction and latency prolongation, whereas only decreased frontal P300 amplitudes were found in carriers without FXTAS. These frontal P300 measures correlated with executive function and information processing speed. Interpretation The neuropsychological testing and ERP results of the present study provide support for the hypothesis that executive dysfunction is the primary cognitive impairment among older female premutation carriers both with and without FXTAS, although these deficits are relatively mild compared to those in FXTAS males. These findings are consistent with a synergistic effect of the premutation and aging on cognitive impairment among older female fragile X premutation carriers, even in those without FXTAS symptoms. Ann Neurol 2013;74:275–283